2020
DOI: 10.1590/0102-672020200004e1552
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy in Octogenarians With Gastric Cancer: Is It Feasible?

Abstract: Background: The octogenarian population is expanding worldwide and demand for gastrectomy due to gastric cancer in this population is expected to grow. However, the outcomes of surgery with curative intent in this age group are poorly reported and it is unclear what matters most to survival: age, clinical status, disease´s stage, or the extent of the surgery performed. Aim: Evaluate the results of gastrectomy in octogenarians with gastric cancer and to verify the factors related to survival. Methods: From pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similarly, in our cohort, we also observed that the incidence of major POC was higher in the high-ALBI group, including the mortality at 30 d and 90 d. One of the justifications for this result is probably related to the age of patients, since high-ALBI group are generally older, as seen in our study. So, it may represent a frail group of patients with a higher risk of complications[ 28 ]. Still, poor nutritional status can contribute to a higher risk of POC[ 29 ], since preoperative hypoproteinemia has already been reported as a risk factor for postoperative infection in gastrointestinal surgery[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our cohort, we also observed that the incidence of major POC was higher in the high-ALBI group, including the mortality at 30 d and 90 d. One of the justifications for this result is probably related to the age of patients, since high-ALBI group are generally older, as seen in our study. So, it may represent a frail group of patients with a higher risk of complications[ 28 ]. Still, poor nutritional status can contribute to a higher risk of POC[ 29 ], since preoperative hypoproteinemia has already been reported as a risk factor for postoperative infection in gastrointestinal surgery[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that those under age 55 years have fewer POC and, as age increases, clinical complications and mortality in 90‐day rise 4,21 . OS after 72 years old is worse and octogenarians have increased risk for postoperative clinical complications 3,4 . However, several confounding factors may influence results: comorbidities increase with age, whereas the functional status decreases; young patients have more aggressive histological characteristics; only elders considered fit enough undergo surgery; and lymphadenectomy is usually restricted in elders.…”
Section: Discussionmentioning
confidence: 99%
“…Although its incidence has decreased, the elderly population with GC has increased in recent years. As surgery is the most effective treatment for resectable GC and life expectancy is rising, the need for surgery in the elderly population is also expected to increase 2–4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel to the increase in life expectancy both nationally and worldwide 11 and the increase in the incidence of biliopancreatic diseases in this population, the performance of ERCP in the elderly has become increasingly frequent because they bring comorbidities inherent to age, such as systemic arterial hypertension, diabetes mellitus, coronary artery disease 13 . Consequently, the performance of ERCP, which is recognized for having lower morbidity and mortality compared to surgical treatment, has been increasingly indicated as a treatment for these biliary and pancreatic diseases.…”
Section: Discussionmentioning
confidence: 99%